Probabilistic Ecological Risk Assessment of OCPs, PCBs, and DLCs in the Haihe River, China - Bin Wang; Gang Yu; Jun Huang; Tai Wang; Hongying Hu (The Scientific World Journal)
The Haihe River is the most seriously polluted river among the seven largest rivers in China. Dichloro-diphenyl-trichloroethanes (DDTs), hexachlorocyclohexanes (HCHs), and PCBs (noncoplanar polychlorinated biphenyls) in the Haihe River, Tianjin were determined using a gas chromatograph – electron capture detector (GC-ECD). Dioxin-like compounds (DLCs) were determined using Chemically Activated LUciferase gene eXpression (CALUX) bioassay. HCH and DDT levels were, respectively, 0.06–6.07 μg/L and ND (not detected) to 1.21 μg/L; PCB levels ranged from 0.12 to 5.29 μg/L; and the total DLCs in sediment were 4.78–343 pg TEQ (toxic equivalency)/g. Aquatic ecological risk assessment was performed using the joint probability curve method and the Monte Carlo-based HQ (hazard quotient) distribution method. The combined risks of similar chemicals and the total risk of dissimilar categories of chemicals were assessed based on the principles of joint toxicity. Due to the adjacent industrial activities, the risk levels of PCBs, DDTs, and HCHs were relatively high. The risk order was as follows: PCBs > DDTs ≈ HCHs > DLCs. The risk of HCHs approximated that of DDTs, which is different from the fact that risk of HCHs is usually much lower in the other Chinese rivers. The total risk caused by these pollutants was very high. Due to their high persistence and potential source from land, the high risks of such pollutants are likely to last for a long period of time.